2016
DOI: 10.1111/bcp.12942
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of studies comparing the medication event monitoring system (MEMS) with alternative methods for measuring medication adherence

Abstract: Different methods are available for measuring medication adherence. In this paper, we conducted a scoping review to identify and summarize evidence of all studies comparing the Medication Event Monitoring System (MEMS) with alternative methods for measuring medication adherence. A literature search was performed using the open database www.iAdherence.org that includes all original studies reporting findings from the MEMS. Papers comparing methods for measuring adherence to solid oral formulations were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 128 publications
7
100
0
1
Order By: Relevance
“…However, their internal validity varies (Cronbachs’s α 0.61–0.91) and their specificity is generally below 75%. Adherence is overreported by up to 20% when compared to an objective measure [23]. These overestimates may be due to a number of reasons, for example social desirability (wanting to be seen as a ‘good’ patient).…”
Section: How To Diagnose Non-adherencementioning
confidence: 99%
See 2 more Smart Citations
“…However, their internal validity varies (Cronbachs’s α 0.61–0.91) and their specificity is generally below 75%. Adherence is overreported by up to 20% when compared to an objective measure [23]. These overestimates may be due to a number of reasons, for example social desirability (wanting to be seen as a ‘good’ patient).…”
Section: How To Diagnose Non-adherencementioning
confidence: 99%
“…Pill-counting overestimates non-adherence by roughly 8% when compared to data from objective electronic monitoring devices [23]. Although in theory it is a simple method, it is entirely dependent on the patient’s cooperation (bringing their pill containers to the clinic), it does not take into account any surplus medication the patient may have from previous prescriptions, and it is time consuming in a busy clinical setting [21].…”
Section: How To Diagnose Non-adherencementioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the Medication Event Monitoring System (MEMS), which is considered a Bgold standard^measure of medication adherence in trial settings. 6 However, it is important to remember that it is an indirect method of measurement-opening the bottle does not equal taking the statin. It is entirely plausible, as the authors discuss, that patients receiving feedback reports were more likely to open the bottle but no more likely to take the medication.…”
mentioning
confidence: 99%
“…7 A review of studies comparing the MEMS with other methods for measuring medication adherence reported that, compared to MEMS, adherence was overestimated by 17 % using self-report, by 8 % using pill count, and by 6 % using rating by a surrogate. 6 Although self-reported medication adherence may overestimate the degree of adherence, it can offer critical insight into patient-specific barriers to medication-taking. 8 For example, the intervention studied by Reddy et al would likely have a greater impact on patients whose main barrier is forgetting to take their medication than on patients whose main concern is cost-related.…”
mentioning
confidence: 99%